Answer:
![x=(12)/(7) \\y=(12)/(5) \\z=-12](https://img.qammunity.org/2021/formulas/mathematics/high-school/7kqqgf72k0vsxv790nf4uy24eximkiwupc.png)
Explanation:
Let's re-write the equations in order to get the variables as separated in independent terms as possible \:
First equation:
![(xy)/(x+y) =1\\xy=x+y\\1=(x+y)/(xy) \\1=(1)/(y) +(1)/(x)](https://img.qammunity.org/2021/formulas/mathematics/high-school/w083a34kendiktqn3u1pjoal87jjhricm7.png)
Second equation:
![(xz)/(x+z) =2\\xz=2\,(x+z)\\(1)/(2) =(x+z)/(xz) \\(1)/(2) =(1)/(z) +(1)/(x)](https://img.qammunity.org/2021/formulas/mathematics/high-school/ijc30iqlbwfkqglbff9nx8vkrpsejo9ykz.png)
Third equation:
![(yz)/(y+z) =3\\yz=3\,(y+z)\\(1)/(3) =(y+z)/(yz) \\(1)/(3)=(1)/(z) +(1)/(y)](https://img.qammunity.org/2021/formulas/mathematics/high-school/150j2rdjvo3rc0jr207l8yuoyv54d2ky52.png)
Now let's subtract term by term the reduced equation 3 from the reduced equation 1 in order to eliminate the term that contains "y":
![1=(1)/(y) +(1)/(x) \\-\\(1)/(3) =(1)/(z) +(1)/(y)\\(2)/(3) =(1)/(x) -(1)/(z)](https://img.qammunity.org/2021/formulas/mathematics/high-school/5a6uqqjlywqexpxgtno23ykhuyvxug7hsg.png)
Combine this last expression term by term with the reduced equation 2, and solve for "x" :
![(2)/(3) =(1)/(x) -(1)/(z) \\+\\(1)/(2) =(1)/(z) +(1)/(x) \\ \\(7)/(6) =(2)/(x)\\ \\x=(12)/(7)](https://img.qammunity.org/2021/formulas/mathematics/high-school/oz6rj4wthh5mrzafgy82pvmcr6ssvrvxux.png)
Now we use this value for "x" back in equation 1 to solve for "y":
![1=(1)/(y) +(1)/(x) \\1=(1)/(y) +(7)/(12)\\1-(7)/(12)=(1)/(y) \\ \\(1)/(y) =(5)/(12) \\y=(12)/(5)](https://img.qammunity.org/2021/formulas/mathematics/high-school/zqb5q5g0ucbb26ego8twqw98wqp1yqnt9o.png)
And finally we solve for the third unknown "z":
![(1)/(2) =(1)/(z) +(1)/(x) \\\\(1)/(2) =(1)/(z) +(7)/(12) \\\\(1)/(z) =(1)/(2)-(7)/(12) \\\\(1)/(z) =-(1)/(12)\\z=-12](https://img.qammunity.org/2021/formulas/mathematics/high-school/wyn2qiv2gr855qeowpqxrnpc76e1pfahr5.png)